Malignant Transformation of Oral Lichen Planus - Sangeeta Wanjari; R S Dolas; Deepashri H Kambalimath (Wolters Kluwer Medknow Publications, 2010)
Oral lichen planus (OLP) is a chronic inflammatory mucocutaneous disease that frequently involves the oral mucosa. It has been regarded by many authors as a premalignant condition. There has been a continuous debate regarding the possible malignant potential of OLP, and these patients have been recommended to have their lesions monitored two to four times annually. A case of a lichen planus transformed into malignancy is reported here. This case does not provide answers to the ongoing controversy about the innate propensity of OLP to become malignant. However, in view of common occurrence of OLP and unresolved issue regarding its malignant potential (MP), thus case report illustrates the need for histologic confirmation and close follow-up of patients with clinical lesions that have lichenoid features.